Sclerotia of a phytopathogenic fungus restrict microbial diversity and improve soil health by suppressing other pathogens and enriching beneficial microorganisms. (1st April 2020) - Mehmood, Mirza Abid; Zhao, Huizhang; Cheng, Jiasen; Xie, Jiatao; Jiang, Daohong; Fu, Yanping
Abstract: Sclerotinia sclerotiorum, a notorious soil-borne pathogen of various important crops, produces numerous sclerotia to oversummer in the soil. Considering that sclerotia may also be attacked by other microbes in the soil, we hypothesized that sclerotia in soil may affect the community of soil microbes directly and/or indirectly. In this study, we inoculated sclerotia of S. sclerotiorum in soil collected from the field to observe changes in microbial diversity over three months using 16S rRNA and ITS2 sequencing techniques. Alpha diversity indices exhibited a decline in the diversity of microbial communities, while permanova results confirmed a significant difference in the microbial communities of sclerotia-amended and non-amended soil samples. In sclerotia-amended soil, fungal diversity showed enrichment of antagonists such as Clonostachys, Trichoderma, and Talaromyces and a drastic reduction in the plant pathogenic microbes compared to the non-amended soil. Sclerotia not only activated the antagonists but also enhanced the abundance of plant growth-promoting bacteria, such as Chitinophaga, Burkholderia, and Dyella. Moreover, the presence of sclerotia curtailed the growth of several notorious plant pathogenic fungi belonging to various genera such as Fusarium, Colletotrichum, Cladosporium, Athelia, Alternaria, and Macrophomina . Thus, we conclude that S. sclerotiorum when dormant in soil can reduce the diversity of soil microbes, including suppressing plant pathogens and enriching beneficial microbes. To the best of our knowledge, this is the first time a plant pathogen has been found in soil that can significantly suppress other pathogens. Our findings may provide novel cues to understand the ecology of crop pathogens in soil and maintaining soil conditions that could be beneficial for constructing a healthy soil microorganism community required for mitigating soil-borne diseases. Highlights: A periodic shift in microbial diversity after the amendment of sclerotia of Sclerotinia sclerotiorum. We used 16S rRNA and ITS2 sequencing techniques. Sclerotia-amended samples activated beneficial microbes and reduced the abundance of phytopathogenic microbes. To the best of our knowledge, this is the first time a plant pathogen has been found to improve soil health.